Living Quran di Era Digital: Analisis Praktik Tadarus Online Selama Ramadhan pada Platform Internet: Penelitian - Lu’luatul Fauziah; Altaf Abdurrohman; Hikmatul Lutfi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In today's digital era, the practice of reciting the Qur'an has undergone a significant transformation, thanks to the presence of various online platforms that make it easier for Muslims to engage in worship through reading the Qur'an, especially during the month of Ramadan. This study analyzes how online tafsir on internet platforms becomes part of the "Living Quran" phenomenon that brings the Qur'an to life interactively and contextually in modern society. With features such as digital text display, multi-language translation, and easy access via mobile devices, online tadarus not only expands the reach of Qur'an learning but also strengthens the consistency and solemnity of worship during the pandemic and post-pandemic. In addition, the existence of virtual communities and online tadarus classes strengthens the social and spiritual aspects, making the Qur'an a source of inspiration for life that is relevant to the challenges of the times. This study also highlights the importance of using technology wisely so that the essence of worship is maintained and the role of digital media as a means of da'wah and Islamic education is more optimal.